Analysis of environment policy development in Colombia (2013)
The development of environment policies in Colombia has been a languid process, which results insufficient facing the challenges of industrial advancements and the excessive demand of raw materials coming from natural resources. Legal failings, inefficient controls and the lack of conscience of several sectors about the irreversible impact caused to the ecosystems constitute the main factors of environment damage